Aflatoxin Problems in Poultry Feed and Its Raw Materials in Indonesia - Sjamsul Bahri (Media Veteriner, 1998)
Contamination of aflatoxins in animal feeds is one of a major problem in the development of poultry industry in Indonesia. Aflatoxins may lead to losses in animal productivity, aflatoxicosis and residue in animal products. A series of investigation on aflatoxin contamination in animal feed in poultry had been carried out at Research Institute for Veterinary Science (Balitvet) between 1984 to 1995. It showed that more than 80 % of commercial chicken feeds were contaminated by aflatoxin B1 (AFBI) within a wide range of concentration. Besides AFB1, other aflatoxins such as AFB2, AFG1 and AFG2 were also found. The level of AFB1 more than 200 ppb was found in 13.5 % out of 193 feed samples, whilst 23.3 % and 63.2 % of samples showed concentration 100-200 ppb and 400 ppb respectively. It had approved from the investigation that corn was the most frequent foodstuff contaminated by aflatoxins compared to other animal foodstuff. Most of corn used for chicken feeds appeared to be the major source of aflatoxin contamination, where it could be indicated visually in bad or good kernel appearance. The levels of AFB1 contamination seemed to be higher in the wet season (39.5 ppb) than in the dry season (19.5 ppb) as well as at the lower altitude (39.8 ppb) was higher than at the higher altitude (24.13 ppb). Based on this view, further studies are required to control of the aflatoxins problems in poultry feed in Indonesia.Key words: aflatoxins, animal feeds, poultry